Controllability of mixed Volterra- Fredholm type Impulsive integro-differential inclusions in Banach spaces (International Journal of Engineering and Computer Science, 2014)
The paper establishes a sufficient condition for the controllability of semilinear mixed Volterra-Fredholm type Impulsive integro-differential inclusions in Banach spaces. We use Bohnenblust-Karlin’s fixed point theorem combined with a strongly continuous operator semigroup. Our main condition only depends upon the local properties of multivalued map on a bounded set. An example is also given to illustrate our main results